Assessing thePrior Intercultural Experiences,Motivating Factorsand Deterrentsinfluencing4-H Members’ Intention to Participate an International Experience Program - Melissa Carter; J. C. Bunch; Shelli Danjean (Journal of International Agricultural and Extension Education, 2016)
International experience programs (IEPs), such as International 4-H Youth Exchange (IFYE) and other programs employed by U.S Cooperative Extension Programs and international partners, can forge students’ development of a global perspective. The purpose of this study was to determine 4-H members’ prior intercultural experience, perceived motivating factors to participation in an IEP, perceived deterrents to participation in an IEP, and 4-H members’ intentions to participate in an IEP; and to explain 4-H members’ intention to participate in an IEP. Results of this study suggest that 4-H members’ intention to participate in an IEP is predicted by prior intercultural experiences. The effect of prior intercultural experiences is mediated by motivating factors, that is as motivating factors increase, intent increases while reducing the effect of prior intercultural experiences. A recommendation for practitioners to use to bridge the gap between 4-H members and other cultures is to provide varied intercultural experiences in or near the youths’ own community
Keywords: Intercultural experiences; motivating factors; deterrents; international experience programs; 4-H